373 Coach education as a strategy to improve adherence to ACL injury prevention programs: a cluster-randomized controlled trial. (3rd March 2020) - Ling, Daphne; Boyle, Caroline; Schneider, Brandon; Janosky, Joseph; Kinderknecht, James; Marx, Robert
Abstract : Background: Despite evidence of its efficacy, ACL injury prevention programs have had limited success in convincing coaches to perform the recommended exercises. Objective: We evaluate a coach education workshop that trains coaches on how to implement an injury prevention program and measure the impact of this strategy on adherence rates. Design: Cluster-randomized controlled trial. Setting: High school sports teams. Participants : Eight high schools were recruited and randomized 1:1 to the intervention or control arm. The intervention schools contained 12 teams (5 girls), and the control schools contained 10 teams (4 girls). The sports included basketball, volleyball, track and field, baseball/softball, and lacrosse. Interventions: Our institution's Sports Safety Program has developed a 90-minute education workshop aimed at coaches that teaches them how to provide exercise instruction and to correct movement deficiencies using feedback cues. The schools in the control arm received print materials on recommended exercises. Main outcome measurements: Coach adherence was the main outcome. Eight data collectors, who were blinded to the team's assignment, were trained to observe a team's practice or game 3 times a week. At each session, they completed a survey to identify the exercise and then answered whether the coach 1) provided exercise instructions and 2) provided feedback cues. Results: A total of 399 practice or game sessions were observed over 2 sport seasons (62% in intervention schools). A higher proportion of coaches in the intervention arm provided exercise instructions (27% vs 21%, p<0.0009). Similarly, more coaches in the intervention arm provided feedback cues to encourage proper technique (15.3% vs 7%, p<0.00001). Conclusions: One barrier to adoption of injury prevention programs may be the coach's lack of knowledge on how to implement a warm-up routine that is effective at reducing ACL injuries. A coach education workshop may lead to actual behavior change in practice.